Political Participation in Elections by New Voters in General: Political Participation in Elections by New Voters in General - Yudhy, Yudhy; Nur’aeni, Nur’aeni (International Journal of Humanities, Law, and Politics, 2023)
In Indonesia, elections are a visible example of democracy and a way for the populace to exercise their power over the state and government. Elections based on Pancasila and the Republic of Indonesia's Constitution from 1945. Within the State Unitary Republic of Indonesia (NKRI), elections were held on the principles of direct, general, free, secret, honest, and fair. Involvement in a democratic party (Election) is a sign that the people are exercising their highest lawful state authority, which is reflected in political participation in a democratic nation. In order to develop legislators and leaders who are aspirational, qualified, and accountable for the welfare of the people, general elections are one of the democratic processes that represent the wealth of the populace. The goal of this paper is to identify the ways in which new voters participate politically in elections, as well as the motivating and impeding reasons. This journal paper employs a literature review as its writing strategy, which is supported by pertinent research findings. By splitting their time between studying and participating in political activities, it is believed that inexperienced voters will engage in politics more actively.